2013
DOI: 10.1111/cid.12121
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between the Bone Density Recorded by a Computerized Implant Motor and by a Histomorphometric Analysis: A Preliminary In Vitro Study on Bovine Ribs

Abstract: Within the limitations of this in vitro study, the intraoperative site-specific classification of bone density, obtained with this innovative system, could be helpful for the clinician to tailor the surgical protocol to the different situations in implant dentistry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
32
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 29 publications
(55 reference statements)
3
32
0
1
Order By: Relevance
“…A previous study found a significant linear correlation between immediate BIC and BMD at the placement site33, which explains the increase in the initial BIC caused by the high BMD in this study. In addition, the average torque values, which reflect bone strength, are known to be significantly correlated with histological bone density data34.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study found a significant linear correlation between immediate BIC and BMD at the placement site33, which explains the increase in the initial BIC caused by the high BMD in this study. In addition, the average torque values, which reflect bone strength, are known to be significantly correlated with histological bone density data34.…”
Section: Discussionmentioning
confidence: 99%
“…This might be reconsidered once implant-motors as described by Iezzi G. et al 21 are generally available.…”
Section: Discussionmentioning
confidence: 99%
“…Iezzi G. et al 21 2013 introduced a computerized implant motor recording ITVs at implant insertion and experimentally found a close correlation between the ITVs recorded by this device and the later histomorphometric analysis pf bone density.…”
mentioning
confidence: 99%
“…A study on bovine ribs has shown that the device provides reliable bone density values, significantly correlating with actual histomorphometric data. 23 When used on patients, the device enabled zones of the jaws with different bone densities to be distinguished. 24 Additionally, the device allows instantaneous insertion torque and other correlated values to be recorded at the time of implant placement.…”
Section: 5005/jp-journals-10024-1743mentioning
confidence: 99%
“…It has also been shown that the torque-depth function integral the device provides at implant insertion, correlates with immediate boneto-implant contact (BIC) at insertion in experiments on bovine ribs, later confirmed by observations on human subjects. 23,25 The device, therefore, seems to convey pivotal information to the surgeon; both, immediately before implant placement, helping to design a proper implantinsertion intraoperative strategy, and just after insertion, allowing assessment of the primary stability achieved. In this study, a case is presented in which bone density data were acquired using both conventional CT scans and the torque-measuring system, in order to get an inthe-field assessment of the advantages provided by the device, if any.…”
Section: 5005/jp-journals-10024-1743mentioning
confidence: 99%